Pelatihan Manajemen Keuangan Dan Etika Bisnis Islami Berbasis Nilai Tasawuf Bagi Pedagang Pasar Ciawi Dalam Upaya Meningkatkan Kemandirian Ekonomi Dan Menghindari Praktik Riba Digital - Iis Amanah Amida; Sani Haryati (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
This community service program aims to enhance the financial management skills and understanding of Islamic business ethics among traders at Ciawi Market through a tasawuf-based (Sufi values) approach. Field observations show that many traders still face difficulties in maintaining simple financial records, separating personal and business finances, and recognizing digital financial practices that may involve usurious (riba) elements. The training program introduced participants to practical financial management, cash flow control, and strategies to avoid digital riba in online transactions. The tasawuf-based approach was implemented to cultivate spiritual awareness, honesty, and integrity in business practices. The methods used included lectures, interactive discussions, financial recording simulations, and online mentoring. The results indicated an 85% increase in participants’ understanding of business financial management and a positive shift in their attitudes toward more ethical and Sharia-compliant business practices. This program contributes to strengthening the traders’ economic independence and fostering an ethical business ecosystem rooted in spiritual and moral values.